Effect of Vaccination with Carrier Protein on Response to Meningococcal C Conjugate Vaccines and Value of Different Immunoassays as Predictors of Protection - Burrage, Moya (American Society for Microbiology, 2002)
In order to plan for the wide-scale introduction of meningococcal C conjugate (MCC) vaccine for United Kingdom children up to 18 years old, phase II trials were undertaken to investigate whether there was any interaction between MCC vaccines conjugated to tetanus toxoid (TT) or a derivative of diphtheria toxin (CRM(197)) and diphtheria-tetanus vaccines given for boosting at school entry or leaving. Children (n = 1,766) received a diphtheria-tetanus booster either 1 month before, 1 month after, or concurrently with one of three MCC vaccines conjugated to CRM(197) or TT. All of the MCC vaccines induced high antibody responses to the serogroup C polysaccharide that were indicative of protection. The immune response to the MCC-TT vaccine was reduced as a result of prior immunization with a tetanus-containing vaccine, but antibody levels were still well above the lower threshold for protection. Prior or simultaneous administration of a diphtheria-containing vaccine did not affect the response to MCC-CRM(197) vaccines. The immune responses to the carrier proteins were similar to those induced by a comparable dose of diphtheria or tetanus vaccine. The results also demonstrate that, for these conjugate vaccines in these age groups, both standard enzyme-linked immunosorbent assays and those that measure high-avidity antibodies to meningococcal C polysaccharide correlated equally well with assays that measure serum bactericidal antibodies, the established serological correlate of protection for MCC vaccines.